Better more than one: Portfolio currency pricing and exchange rate hedging - Maria V. Sokolova (Graduate Institute of International and Development Studies, 2016)
This paper examines the relationship between the composition of exporters' currency pricing portfolio - number and value of product sales in different currencies at a destination - and their success in trade as measured by continuing to their exporting activity. Detailed investigation of currency choice data of Russian exporters between 2005-2009 shows that many exporters use only one currency pricing per destination. Among those who use more than one currency pricing, higher diversification is indeed associated with up to 18% higher odds of survival as an exporter at the product-destination. Nevertheless, many exporters still use only one currency pricing per destination. This puzzle is explained in this paper by incorporating the concept of "exchange rate hedging costs" into the existent literature on currency choice. These costs are firm-specific and relate to the complexity on the part of the firm of using more than one currency. The firms that have high exchange rate hedging costs will be using only one currency, but still continue exporting to the destination.
Keywords: F14; F31; F36; F41; G11; 330; international currency choice; currency portfolio; exchange rate; export data; vehicle currency; emerging economy; exchange rate hedging